Neurobiology and the Financial Paradigm at the Turn of the 21st Century - Michalski, Tomasz (Journal of Finance and Financial Law, 2025)
The purpose of the article. The paper aimed to investigate how the brain functions established through the process of evolution influences decisions regarding the activities of entities on the financial market and how this affects changes in the behavior of these entities on the market. Additionally, it aimed to understand the definitions of basic concepts and thus contribute to changing the financial paradigm. Methodology. The research uses a method based on a review of literature from fields dealing with the issues raised in the topic, such as behavioral economics, finance, and neurobiology. Results of the research. It was pointed out that the turn of the 20th and 21st centuries was a period of intensification of phenomena that fostered the emergence of anomalies, thus signaling symptoms of chaos in the financial world. Phenomena such as the information and digital revolution, increasing financialization, and chrematistics were identified, which are, among other things, the result of the implementation of the growth dogma, obligatory for homo oeconomicus for thousands of years. The fact of the progressive departure from ethical and moral values in all types of activities was emphasized. In these conditions, the decisions/actions of entities operating on the financial market cause changes in the understanding of basic concepts to be observed and, consequently, tendencies to change the definitions of these concepts, leading to a departure from the current financial paradigm.